Assessing Physical Fitness of Incoming Sports Students to Set Minimum Thresholds for Universitas Negeri Makassar Admission - Muhammad Rizky Alfarizi; Dewangga Yudhistira; Andi Muhammad Rizky Al Mufarid; Wildayati Wildayati; Sitti Fatimah Azzahra (CV Lentera Cendekia Indonesia, 2025)
ABSTRACT Intorduction. The aim of the research is to portray the physical fitness status of students at a single point in time without comparing fitness-test results over time, Physical fitness quality becomes one of the key criteria — alongside academic achievement — for competing with other sports faculties, allowing the university to maintain high competitiveness in academic, athletic, and industry domains Methods. This study employed a quantitative approach with a cross-sectional and descriptive design Results. Standing Broad Jump, 9.72% fell in the low category, 38.89% in medium, and 41.67% in high; for Push‑Up, 12.50% low, 27.78% medium, and 43.06% high; for Sit‑Up, 13.89% low, 33.33% medium, and 43.06% high; and for Back‑Up, 13.89% low, 31.94% medium, and 44.44% high. Standing Broad Jump, 7.14% fell in the low category, 57.14% in medium, and 35.71% in high; for Push-Up, 21.43% in low, 28.57% in medium, and 50.00% in high; for Sit-Up, 5.00% low, 21.43% medium, and 42.86% high; and for Back-Up, 7.14% low, 50.00% medium, and 42.86% high. Conclusion. Push-ups 30–40 times/minute (men) and 20–30 times/minute (women). Sit-ups in one minute ≥ 30–35 times (men)/ ≥ 25–30 times (women), Back-up 1 minute ≥ 60–65 (test units: repetitions/duration/backup test score). Standing long jump target 230 cm (men), 200 cm (women)